Answer (4):
a=ub/k because
u=ak/b (starting equation)
ub=ak (multiply b to both sides)
a=ub/k (divide both sides by k)
Answer (6)
x=g+c-y because
g=x-c+y (starting equation)
x+y=g+c (add c to both sides)
x=g+c-y (subtract y from both sides)
Answer:
575x.25=143.75 575-143.75=$431.25
21.95x.15=$3.29 tip total bill $25.24
Step-by-step explanation:
Answer:
x = 9
Step-by-step explanation:
The product of the external part and the entire part of one secant is equal to the product of the external part and the entire part of the other secant, that is
5(x - 6 + 5) = 4(x - 3 + 4)
5(x - 1) = 4(x + 1) ← distribute parenthesis on both sides
5x - 5 = 4x + 4 ( subtract 4x from both sides )
x - 5 = 4 ( add 5 to both sides )
x = 9
Answer:
Step-by-step explanation:
(35/5) - 5
7 - 5 = 2